2022
DOI: 10.1101/2022.07.02.498571
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pollen sequencing reveals barriers and aberrant patterns of recombination in interspecific tomato hybrids

Abstract: Tomato is the most consumed vegetable in the world. Increasing its natural resistance and resilience is key for ensuring food security within a changing climate. Plant breeders improve those traits by generating crosses of cultivated tomatoes with their wild relatives. Specific allele introgression relying on meiotic recombination, is hampered by structural divergence between parental genomes. However, previous studies of interspecific tomato hybridization focused in single cross or lacked resolution due to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…Introgression in barley is rapidly driven to fixed homozygosity, as expected for a strictly self-fertilising species (Dreissig et al, 2020). Crossovers, recombination and introgression were also found to be nearly absent in the centromeric and pericentromeric regions in Mimulus cardinalis (Nelson et al, 2021) and tomatoes (Demirci et al, 2017;Fuentes et al, 2020) (with the exception of scattered recombination hotspots in these regions: Fuentes et al, 2022b).…”
Section: Evidence For the Role Of Pericentromeric Regions In Reproduc...mentioning
confidence: 87%
See 2 more Smart Citations
“…Introgression in barley is rapidly driven to fixed homozygosity, as expected for a strictly self-fertilising species (Dreissig et al, 2020). Crossovers, recombination and introgression were also found to be nearly absent in the centromeric and pericentromeric regions in Mimulus cardinalis (Nelson et al, 2021) and tomatoes (Demirci et al, 2017;Fuentes et al, 2020) (with the exception of scattered recombination hotspots in these regions: Fuentes et al, 2022b).…”
Section: Evidence For the Role Of Pericentromeric Regions In Reproduc...mentioning
confidence: 87%
“…Many plant studies have also demonstrated that recombination rate is lower in pericentromeric regions, including in common beans (Bhakta et al, 2015), wheat (Jordan et al, 2018), barley (Dreissig et al, 2019;Dreissig et al, 2020), rice (Fayos et al, 2022) and white campion (Filatov, 2023). Others have shown that crossover rate (which is directly correlated with recombination rate) is lower in these regions in tomatoes (Demirci et al, 2017;Fuentes et al, 2020, Fuentes et al, 2022b and wheat (Jordan et al, 2018). Nyine et al (2020) also showed that introgression is less frequent in lowrecombining regions in winter wheat and its relatives.…”
Section: Evidence For the Role Of Pericentromeric Regions In Reproduc...mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the large BSA peak on chromosome 9 overlaps with the Tm-2 a introgression of S. peruvianum in AC- Tm-2 a and the long causative region of aer on chromosome 4 appears to be related to S. pimpinellifolium . These two regions with a distant genetic origin possess abundant polymorphisms between the parental lines, which can lead to recombination “cold spots” (Chetelat et al 2000 ; Fuentes et al 2022 ) and result in very few recombination events through these regions (Figure S5 ). The pool of 45 AR + lines did not show the extreme AR phenotype of aer , since the additional causative loci segregated randomly in the F 2 lines.…”
Section: Discussionmentioning
confidence: 99%